Intrapartum test for detection of Group B Streptococcus colonization during labor. (17th December 2018) - Picchiassi, Elena; Coata, Giuliana; Babucci, Giulia; Giardina, Irene; Summa, Valentina; Tarquini, Federica; Centra, Michela; Bini, Vittorio; Cappuccini, Benito; Di Renzo, Gian Carlo
Abstract: Purpose: The purpose of this study was to evaluate the potential improvement of introducing an intrapartum test for the detection of Group B Streptococcus (GBS) during labor and to estimate its cost-effectiveness versus antepartum GBS screening culture. Materials and methods: Three hundred and thirteen women at beginning of labor, with unknown GBS status or with antepartum GBS screening culture were enrolled. A vaginal–rectal specimen was collected from each woman for GBS detection by real-time PCR. Results of intrapartum test and antepartum GBS screening culture were compared. Results: Antepartum culture results did not always reflect the intrapartum maternal GBS colonization status since in 15.1% of the cases it was not concordant with intrapartum test. However, selecting only women, who underwent antepartum culture and intrapartum test at the same time, the percentage of concordance was 96.6%. Based on intrapartum test results, 74.9% of the total number of intrapartum antibiotic prophylaxis (IAP) was administered uselessly, while 1.9% of women did not receive IAP although they were positive to intrapartum test. Intrapartum test resulted less cost-effective than antepartum culture but it became more cost-effective at a cost threshold of about 16.00 €. Conclusions: The clinical introduction of intrapartum test could be a valuable mean for identification of GBS colonization during labor, allowing an appropriate management of mothers and neonates with consequent benefit for their health and with limited costs for Healthcare System.